Optimal Policy for Macro-Financial Stability - Gianluca Benigno; Huigang Chen; Christopher Otrok; Alessandro Rebucci; Eric Young (Inter-American Development Bank (IDB), 2012)
This paper studies whether policymakers should wait to intervene until a financial crisis strikes or rather act in a preemptive manner. This question is examined in a relatively simple dynamic stochastic general equilibrium model in which crises are endogenous events induced by the presence of an occasionally binding borrowing constraint as in Mendoza (2010). First, the paper shows that the same set of taxes that replicates the constrained social planner allocation could be used optimally by a Ramsey planner to achieve the first best unconstrained equilibrium: in both cases without any precautionary intervention. Second, the paper shows that the extent to which policymakers should intervene in a preemptive manner depends critically on the set of policy tools available and what these instruments can achieve when a crisis strikes. For example, in the context of the model, it is found that, if the policy tools are constrained so that the first best cannot be achieved and the policymaker has access to only one tax instrument, it is always desirable to intervene before the crisis regardless of the instrument used. If, however, the policymaker has access to two instruments, it is optimal to act only during crisis times. Third and finally, the paper proposes a computational algorithm to solve Markov-perfect optimal policy for problems in which the policy function is not differentiable.
Keywords: E52; F37; F41; 330; Finanzkrise; Wirtschaftspolitik; Bankenaufsicht; Konjunkturpolitik; Schuldenübernahme; Dynamisches Gleichgewicht; Theorie